Ethylene Insensitivity Modulates Ozone-Induced Cell Death in Birch - Vahala, Jorma (American Society of Plant Biologists, 2003)
We have used genotypic variation in birch (Betula pendula Roth) to investigate the roles of ozone (O(3))-induced ethylene (ET), jasmonic acid, and salicylic acid in the regulation of tissue tolerance to O(3). Of these hormones, ET evolution correlated best with O(3)-induced cell death. Disruption of ET perception by transformation of birch with the dominant negative mutant allele etr1-1 of the Arabidopsis ET receptor gene ETR1 or blocking of ET perception with 1-methylcyclopropene reduced but did not completely prevent the O(3)-induced cell death, when inhibition of ET biosynthesis with aminooxyacetic acid completely abolished O(3) lesion formation. This suggests the presence of an ET-signaling-independent but ET biosynthesis-dependent component in the ET-mediated stimulation of cell death in O(3)-exposed birch. Functional ET signaling was required for the O(3) induction of the gene encoding β-cyanoalanine synthase, which catalyzes detoxification of the cyanide formed during ET biosynthesis. The results suggest that functional ET signaling is required to protect birch from the O(3)-induced cell death and that a decrease in ET sensitivity together with a simultaneous, high ET biosynthesis can potentially cause cell death through a deficient detoxification of cyanide.